Corona virus disease 2019 pandemic: Ensuring capacity building and outbreak readiness in Iraq - Saurabh RamBihariLal Shrivastava; Prateek Saurabh Shrivastava (Wolters Kluwer Medknow Publications, 2020)
The battle against coronavirus disease-2019 (COVID-19) pandemic is on and each and every nation is trying out to minimize the impact of the disease in their settings. In the Eastern Mediterranean region, a total of 20 nations has reported cases, of which Iraq has reported 728 cases and 52 deaths. It is worth remembering that Iraq has been exposed to multiple challenges in the recent few years, including experiencing internal conflicts or massive displacement of the human population in the nation. All these factors together significantly enhance the probability of the emergence of a major outbreak in the nation, which might go beyond the capacity of the nation to contain, if we do not act now and that too fast. In conclusion, the COVID-19 pandemic continues to expand in most of the affected nations, and the same has been anticipated for Iraq as well in the coming weeks. Thus, the national leaders and supporting agencies have to prepare the health system of the nation for the upcoming battle and reduce the caseload and the probability of disease transmission.